Ultrasonic scattering from compressible cylinders including multiple scattering and thermoviscous effects - Hasheminejad, Seyyed M.; Alibakhshi, M. A. (Archives of Acoustics, 2006)
This paper presents a study of acoustic scattering by a pair of parallel circular thermoviscous fluid cylinders submerged in an unbounded viscous thermally conducting medium. The translational addition theorem for cylindrical wave functions, the appropriate wave field expansions and the pertinent boundary conditions are employed to develop a closed-form solution in the form of infinite series. The analytical results are illustrated with a numerical example in which two identical thermoviscous fluid cylinders are insonified by a nearby parallel acoustic line source at broadside/end-fire incidence. The backscattered pressure amplitude is numerically evaluated and discussed for representative values of the parameters characterizing the system. The effects of source position, transmission frequency and proximity of the two cylinders are examined. Particular attention has been focused on multiple scattering interactions as well as thermoviscous effects. The imperative influence of thermoviscosity on the analysed phenomena is revealed by notable reduction of backscattering amplitude at intermediate and high frequencies. The numerical results also show that the multiple scattering interaction effects are of great (moderate) consequence for end-fire (broadside) incidence at small separations of the cylinders. A limiting case involving a pair of ideal compressible fluid cylinders is considered and a fair agreement with preceding solutions is established.